2019
DOI: 10.13168/cs.2019.0023
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Phosphoric Acid Treatment of Zinc Oxide for Nobel White Pigments

Abstract: Zinc oxide that has the photocatalytic activity is used as white pigment for cosmetics. A certain degree of sebum on the skin is decomposed by the ultraviolet radiation in sunlight. In this work, zinc oxide was shaken with phosphoric acid to synthesize a white pigment for cosmetics. Zinc oxide was set with 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The resulting samples were suitable as white pigments, as all samples showed more than 90. In a previous study [20], some samples prepared with uncondensed phosphoric acid had an L* value of less than 90. It was found that the condensed phosphate solution was superior in maintaining high whiteness.…”
Section: Cosmetic Propertiesmentioning
confidence: 85%
See 2 more Smart Citations
“…The resulting samples were suitable as white pigments, as all samples showed more than 90. In a previous study [20], some samples prepared with uncondensed phosphoric acid had an L* value of less than 90. It was found that the condensed phosphate solution was superior in maintaining high whiteness.…”
Section: Cosmetic Propertiesmentioning
confidence: 85%
“…5 shows UV-vis reflectance spectra of samples treated in various P/Zn ratios for 6 h. All samples indicated high reflectance at the visible light region. Zinc phosphate had high reflectance at the ultraviolet range, therefore samples were expected to have some reflectance at that range [19,20]. However, the reflectance of all the samples prepared in this study was low in the ultraviolet region due to the low reaction rate.…”
Section: Cosmetic Propertiesmentioning
confidence: 85%
See 1 more Smart Citation
“…Zinc phosphate particles without photocatalytic activity were too large, while zinc oxide particles with a smaller particle size had photocatalytic activity. In a previous study, zinc oxide was shaken in phosphoric acid at 30, 40, and 50 °C to obtain zinc oxide particles coated with zinc phosphate [13]. The target particles have a core-shell structure with a core of zinc oxide and a shell of zinc phosphate without photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide was added to 50 mL of the above condensed phosphate solution or condensed phosphoric acid at a P/Zn molar ratio of 1/2 in a glass tube. These mixtures were shaken in hot water (50 ºC) at a shaking rate of 100 times/min for 1 h [13,14]. The powder samples were decanted, washed with water, and dried at 50 ºC over 3 days.…”
Section: Introductionmentioning
confidence: 99%